Mapping the Social and Solidarity Economy in the Municipality of Santa Fe (Argentina): Creation of an updated Database of the Different Experiences - Cardozo, Lucas Gabriel; Serafino, Eugenio; Sotto, Orlando; Tealdo, Julio Claudio (Cooperativismo & Desarrollo, 2017)
Purpose: The paper aims to present a socio-territorial mapping of the expressions of social and solidarity economy in Santa Fe. Topics: Specific bibliography about Social and Solidarity Economy was consulted, as well as different sources that emphasize on the importance and on studies and surveys carried out in Latin American countries. Development: To draw up the maps secondary sources that provided the corresponding data were consulted. The data was then processed and represented with a geographic information system. Conclusions: The results obtained constitute a first and primary source of information, taking into account that there is no previous work with these characteristics for the territory in question. This article is an important basis for elucidating the situation of old and new traditions of the Social and Solidarity Economy with the key referents of Santa Fe. It is expected that the obtained results will be used as a platform to design and implement various work proposals to solve problems of the experiences given in the field of public policies.